2011
DOI: 10.11120/ital.2011.10010078
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Requirements for Supporting Introductory Programming

Abstract: The problems associated with learning and teaching first year University Computer Science (CS1) programming classes are summarized showing that various support tools and techniques have been developed and evaluated. From this review of applicable support the paper derives ten requirements that a support tool should have in order to improve CS1 student success rate with respect to learning and understanding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(17 citation statements)
references
References 24 publications
0
14
0
3
Order By: Relevance
“…The enhanced message appears alongside the original as recommended by [6]. If no enhanced error message is possible the user is presented with a statement indicating the line number of the first error, and referring the user to the standard javac output which is in the same window (see Figure 1).…”
Section: The Tool and Methodsmentioning
confidence: 99%
“…The enhanced message appears alongside the original as recommended by [6]. If no enhanced error message is possible the user is presented with a statement indicating the line number of the first error, and referring the user to the standard javac output which is in the same window (see Figure 1).…”
Section: The Tool and Methodsmentioning
confidence: 99%
“…The interest is particularly linked to the issue of teaching algorithms and programming concepts to first year science major at Moroccan high schools. Our literature study reveals that several difficulties arise during the learning process of basic programming concepts such as program construction (Lahtinen, Ala-Mutka, & Järvinen, 2005), loops manipulation (Ginat, 2004), structures control and algorithms (Seppälä, Malmi, & Korhonen, 2006) Other studies suggested that these difficulties are mainly due to poor teaching methodologies, low interaction levels with students in class and lack of interest (Barker, McDowell, & Kalahar, 2009;Coull, & Duncan, 2011) The lack of interest of novice students is usually attributed to the fact that these students find programming full of tedious theoretical concepts and techniques (Bennedsen, Caspersen, & Kölling, 2008). Among the solutions to overcome these difficulties aforementioned, there's a call to change the programming working environment for students (Kelleher, & Pausch.…”
Section: Introductionmentioning
confidence: 99%
“…Aynı zamanda öğretim metodundan kaynaklı olarak da programlama dersinde öğrenciler zorluk yaşayabilmektedir. Birçok araştırmada belirtilen zorluklara karşı programlama öğretiminin nasıl olması gerektiği tartışılmaktadır (Coull ve Duncan, 2011;Lahtinen vd., 2005).…”
Section: Introductionunclassified